The Impact of Education towards Mother’s Knowledge About Stunting Prevention Using Moringa Oleifera in Kuan Noel Village, Fatumnasi District, South Central Timor Regency - Irlin Falde Riti; Emanuel Suban Bala Lewar (Alma Ata University Press, 2020)
One of nutritious problems susceptibly encountred in the world nowadays is kid’s stunting. Stunting is a failure of growth condition and cronical nutritious problems caused by poor nutritious supply because of improper meal provisions in long term growth consumptions. Stunting could be primarily prevented by increasing knowledge about stunting prevention through consuming moringa oleifera regularly. This study is intended to know the impact of education towards mother’s knowledge about stunting prevention through regular moringa oleifera consumption. This research applied a quasi experimental design by generating non equivalent control group which complied two groups; 30 subjects (mothers) were considered as treatment group; whereas, other 30 subjects (mothers) were taken as control group. Thus sampling technique applied was consecutive sampling. The study showed that there was a significant impact on education score after intervention towards the treatment group (p=0,000); whereas there was no significant difference on the control group (p=0,184). The statistical analysis applied was independent sample t-test which showed that education was significantly impacted the increase of mother’s knowledge (p=0,000). It means that education had impact towards mother’s knowledge about stunting prevention using moringa oleifera.